LANGUAGE POLITENESS PRINCIPLE IN INDONESIA LAWYERS CLUB TALKSHOW ON TV ONE - Aditya Mahendra Ariputra; Muhammad Rohmadi; Sumarwati Sumarwati (IAIN MADURA, 2018)
Indonesia Lawyers Club is a television program by TV ONE aired every Tuesday at 19:30 to 22:00 p.m and discussed the issues being discussed by the Indonesian people at that time. Indonesia Lawyers Club is a program in a talk show format, presenting experts discussing law, politics, religion, crime. From this event, people see a problem not only from a single point of view but from different perspectives. This happens because this talk show presented many experts in their fields, both for the pro and on the counter. Experts argue their opinions according to the channel hosted by a host named Karni Ilyas. This research has a purpose to explain the fulfillment of the politeness principle of language in talk show Indonesia Lawyer Club viewed from Leech’s perspective. This research is descriptive qualitative one. Data collection techniques were used were Uninvolved Conversation Observation Technique (SBLC), recording technique, and note-taking. The data obtained was described using a descriptive development pattern. This study showed the results of the fulfillment of usage of language politeness principle which included 6 maxims, they were maxim of wisdom, maxim of acceptance, maxim of mercy, maxim of humility, maxim of suitability, and maxim of conclusion.